Metachronous colorectal cancer risk for mismatch repair gene mutation carriers: the advantage of more extensive colon surgery. Issue 7 (30th December 2010) - Parry, Susan; Win, Aung Ko; Parry, Bryan; Macrae, Finlay A; Gurrin, Lyle C; Church, James M; Baron, John A; Giles, Graham G; Leggett, Barbara A; Winship, Ingrid; Lipton, Lara; Young, Graeme P; et al.
Abstract : Background: Surgical management of colon cancer for patients with Lynch syndrome who carry a mismatch repair (MMR) gene mutation is controversial. The decision to remove more or less of the colon involves the consideration of a relatively high risk of metachronous colorectal cancer (CRC) with the impact of more extensive surgery. Objective: To estimate and compare the risks of metachronous CRC for patients with Lynch syndrome undergoing either segmental or extensive (subtotal or total) resection for first colon cancer. Design: Risk of metachronous CRC was estimated for 382 MMR gene mutation carriers (172 MLH1, 167 MSH2, 23 MSH6 and 20 PMS2 ) from the Colon Cancer Family Registry, who had surgery for their first colon cancer, using retrospective cohort analysis. Age-dependent cumulative risks of metachronous CRC were calculated using the Kaplan–Meier method. Risk factors for metachronous CRC were assessed by a Cox proportional hazards regression. Results: None of 50 subjects who had extensive colectomy was diagnosed with metachronous CRC (incidence rate 0.0; 95% CI 0.0 to 7.2 per 1000 person-years). Of 332 subjects who had segmental resections, 74 (22%) were diagnosed with metachronous CRC (incidence rate 23.6; 95% CI 18.8 to 29.7 per 1000 person-years). For those who had segmental resections, incidence was statistically higher than for those who had extensive surgery ( P <0.001). Cumulative risk of metachronous CRC was 16% (95% CI 10% to 25%) at 10 years, 41% (95% CI 30% to 52%) at 20 years and 62% (95% CI 50% to 77%) at 30 years after segmental colectomy. Risk of metachronous CRC reduced by 31% (95% CI 12% to 46%; p=0.002) for every 10 cm of bowel removed. Conclusions: Patients with Lynch syndrome with first colon cancer treated with more extensive colonic resection have a lower risk of metachronous CRC than those receiving less extensive surgery. This finding will better inform decision-making about the extent of primary surgical resection.